Spontaneous pneumomediastinum in patients with COVID-19. Case report. - Sotelo-Jiménez, Pedro Paolo (2021)
Introduction: Pneumomediastinum is an infrequent and rare pathology. The typical radiological manifestations in patients with SARS-CoV-2 pneumonia consist of the presence of bilateral pulmonary opacities, of peripheral distribution. In a recent series of patients with COVID-19, it indicates that 1% of patients can develop spontaneous pneumomediastinum as a complication, it is generally benign and it is not yet clear that this may be an indicator of worsening. Clinical Case: This is a 43-year-old male patient who presented a 15-day illness characterized by pharyngeal pain, fever, chest pain and respiratory distress, receiving multiple antiviral and antibiotic treatment schemes without response, for which he attended to Rebagliati Hospital where he was found respiratory failure, hypoxemia and sepsis. His tomography was compatible with ground glass infiltrate, areas of bilateral lung consolidation, and pneumomediastinum. It did not require surgical treatment and it evolved favorably to pneumonia with a decrease in inflammatory markers and remission of pneumomediastinum in tomographic control. Conclusion: This report highlights that in COVID-19 infection the pulmonary complications to take into account are bilateral pneumonia, bacterial coinfection, sepsis and spontaneous pneumomediastinum.